Sensor-networks-based mobile system for health care - Aung, Ma Moh Moh (2010)
This project report presents a design of an autonomous Stair Climbing Robot which can travel on the plane surface and climb to the staircase. The prototype of the climbing robot is built in such a way that its electronics and mechanical complexity are reasonable and practical. The hardware and software implementations are involved in this project in order to meet the design criteria for our prototype. The hardware development mainly involves electronics hardware and mechanical hardware. The prototype is designed with two tracked mechanisms and it is built from the scratch. Later on, it is mounted with electronics hardware components to perform the desired functionalities. It also has the visual capability through vision sensors and wireless communication capability from host PC to sensors network and the micro-controller.The robot’s motion along the predefined path is controlled using fuzzy logic controller. The fuzzy rules are developed for deciding when to process information from each of the sensors. The input signals from the sensors are sent to micro-controller one at a time. The real-time embedded software for the microcontroller is developed in C language. Experimental results show the climbing robot prototype built in this project have met the desired functionalities.